Solubility of Two Resin Composites in Different Mouthrinses. (7th April 2014) - Ozer, Sezin; Sen Tunc, Emine; Tuloglu, Nuray; Bayrak, Sule
Abstract : Aim . This study aimed to compare the solubility of a universal restorative resin composite (Filtek Z250; FZ250) and a silorane-based resin composite (Filtek Silorane; FS) after immersion in alcohol-containing mouthrinse, alcohol-free mouthrinse, and artificial saliva. Methods . 30 discs (10 mm × 1 mm) were prepared from each material and desiccated until a constant mass was obtained. Specimens were immersed in the test solutions for two days and desiccated again. Solubility was calculated based on the change in weight of each specimen before and after immersion. Data was analyzed using two-way ANOVA and Tukey's Post Hoc test P < 0.05 . Results . Solubility values for both resin composites were the highest in the alcohol-containing mouthrinse. FZ250 showed greater solubility than FS; the difference was only significant in artificial saliva. Conclusion . Both resin-composite materials tested exhibited some degree of solubility in each of the test solutions. The use of an alcohol-free mouthrinse may be preferable for patients with extensive composite restorations.